2020
DOI: 10.1186/s40981-020-00334-7
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal administration of nusinersen for spinal muscular atrophy: report of three cases with severe spinal deformity

Abstract: Background: Spinal muscular atrophy (SMA) is a genetic disease characterized by degeneration of the spinal cord, resulting in progressive muscle atrophy. Recently, nusinersen has been approved for treating SMA, which should be administered intrathecally. Case presentation: Patient 1 was a 36-year-old woman with SMA type 2. Patients 2 and 3 were 10-and 17-year-old girls with SMA type 1. In patients 1 and 2, the needle was inserted into the spinal column, but outflow of cerebrospinal fluid was unable to be confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Intrathecal (IT) access is commonly established using the landmark technique in normal subjects. However, patients with SMA are affected by severe scoliosis [ 3 5 ] and are often with vertebral instrumentation [ 3 , 4 ]. In those patients, landmarks for intrathecal access can be difficult to identify, and fluoloscopy and real-time computed tomography (CT)-guided puncture have been shown to help access an intrathecal space [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intrathecal (IT) access is commonly established using the landmark technique in normal subjects. However, patients with SMA are affected by severe scoliosis [ 3 5 ] and are often with vertebral instrumentation [ 3 , 4 ]. In those patients, landmarks for intrathecal access can be difficult to identify, and fluoloscopy and real-time computed tomography (CT)-guided puncture have been shown to help access an intrathecal space [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As reported, higher termination of dural sac in some SMA patients may limited the use of L5–S1 interspace for lumbar puncture [ 25 ]. In our cohort, attempt has been made to administrate nusinersen intrathecally via L5–S1 interval in 1 of the 2 patients with L5 as lowest instrumented vertebra but in vain.…”
Section: Discussionmentioning
confidence: 99%
“…Cartwright MS et al also reported only 74% of patients with SMA and complicated spines were injected via lumbar puncture under fluoroscopic guidance, and others required alternative strategies for intrathecal injection of Nusinersen 10) . In some SMA patients with spinal deformity, the dural sac sometimes terminates at around the level of L 5, which is considered higher than normal 11) . Therefore, an intrathecal approach is considered difficult at L5/S1 level in patients with spinal deformity.…”
Section: Discussionmentioning
confidence: 99%